Biodegradation of Naphthalene by Local Fungal Isolates - B. Mohammed, Duha; H .Al-Jubouri, Muna; Husein Khudeir, Saad (Iraqi Journal of Science, 2023)
Three hundred and twelve (312) local fungal isolates were isolated from sixty four (64) different contaminated soil samples with oil wastes at different periods, using potato dextrose agar (PDA).the fungal isolates were tested for its ability to degrade naphthalene .Primary and secondary screening were done using solid (MSM) and liquid (MSM) with 100ppm naphthalene and pH 7 respectively. Results from Primary screening showed that 25 isolates gave good growth, 47 gave moderate growth, 66 gave weak growth and 174 were never growing. According to above results 25 fungal isolates were tested for its ability to degredade naphthalene using liquid mineral media (MSM) pH7,100ppm naphthalene and incubated at 30 0C 120rpm for 7 days. Reduction of naphthalene concentration was estimated by using HPLC and Horiba analysis. Results showed that Ti, Mi, Ru isolates appeared highest ability to consume naphthalene (87.7), (88.1), (87.6) % respectively. According to Macro and Microscopic featured the isolates Ti, Mi, Ru were subsequently identified as Aspergillus niger, Trichoderma viridi and Fusarium verticelloides respectively.